Efficiency Level of Health Spending Governments: Evidence from North Maluku Indonesia - Prince Charles Heston Runtunuwu; Mochamad Roland Perdana (Jurnal Ekonomi dan Studi Pembangunan, 2024)
This study aims to determine and analyze the level of technical efficiency, cost, technical systems and corrective steps that need to be taken by inefficient regions in 10 regencies/cities in North Maluku Province in 2016-2020. This research uses secondary data from 10 districts/cities in North Maluku Province. The variables used include the APBD expenditure variable according to the health function as input, the variable number of puskesmas, posyandu, medical personnel and midwives at puskesmas and government hospitals as intermediate output variables and the variable Infant Mortality Rate (IMR), Maternal Mortality Rate (AKI), Number Life Expectancy (AHH) and Human Development Index (IPM) as outcome output variables. This research method uses Data Envelopment Analysis (DEA) with the assumption of Variable Return to Scale (VRS) and is input oriented. The results obtained are an average cost technical efficiency of 0%, while the technical efficiency of the system reaches 70%, so that there are indications of inefficiency in the allocation of health sector spending and corrective measures are needed based on the potential for regional improvement which are still not efficient so that the proportion of input and output can be efficient according to the needs of each region.